Bilateral alterations in sensorimotor function and altered sensory strategy in individuals with unilateral chronic ankle instability - Xiaomei Hu; Xihe Hou; Lin Wang (Journal of Exercise Science & Fitness)
Objective: This study aimed to evaluate bilateral sensorimotor function in patients with unilateral CAI. Furthermore, sensory reweighting ability and vestibular modulation were assessed. Methods: Twenty individuals with unilateral CAI and twenty healthy controls participated in this study. All participants executed ankle proprioception, plantar sensation, unilateral stance, Y balance, motor control test (MCT) and sensory organisation test (SOT) assessments. Proprioception assessment included joint position sense and force sense (FS), and plantar sensation evaluation consisted of light-touch, vibration and two-point discrimination (TPD) thresholds at the heel, head of the first metatarsal (1 MF), base of the fifth metatarsal (5 MF), centre of foot and forefoot. MCT and SOT tests were conducted using NeuroCom Balance Manager System. Except for SOT, all tests evaluated bilateral limbs, and the order of limbs was randomly selected. 2 (group) × 2 (limb) mixed model analyses of variance were performed for outcome measures of unilateral stance, Y balance and MCT, and independent t-test was used to analyse the outcomes of SOT between two groups. Mann–Whitney U and Wilcoxon test were applied to examine the differences in plantar sensation between groups and limbs. Results: For plantar sensation, increased light-touch threshold at heel and 1 MF and the TPD threshold at 1 MF were observed bilaterally in CAI group (p < 0.05). No differences were observed in joint position sense (JPS), but bilateral deficit was found in plantarflexor FS with moderate effect size (uninjured side: ES = 0.67; injured side: ES = 0.61) in CAI group. For unilateral stance with eyes closed, moderate postural instability was displayed bilaterally in the anteroposterior direction (uninjured side: ES = 0.71; injured side: ES = 0.86). The delayed latency of MCT with medium-backward translation was also observed in both sides of unilateral CAI (uninjured: ES = 0.74; injured: ES = 0.92). Compared with healthy controls, higher visual reliance was shown moderately in the injured and uninjured sides of unilateral CAI (uninjured: ES = 0.78; injured: ES = 0.91). Sensory analysis of SOT displayed decreased use of visual (p = 0.001) and vestibular information (p < 0.000) in CAI group. Conclusion: Unilateral CAI presented impaired plantar sensation and ankle proprioception on both sides. Higher visual reliance, delayed motor response and postural instability under unreliable visual clues were also displayed bilaterally. Except for bilateral sensorimotor alterations, reduced ability of sensory reweighting and fixed sensory strategy also presented in CAI group, but the somatosensory clue still served as the main sensory source in CAI.